Research of Tooth Profile Topcut of Real-time Zero-clearance Steel Ball Precision Transmission based on Envelope Method - Sun Pengfei; An Zijun (Jixie chuandong)
Whether practical tooth profile of real-time zero-clearance steel ball precision transmission is topcut directly affects its transmission performance. Based on the envelope method,the tooth profile topcut issue of real-time zero-clearance steel ball precision transmission is indepth study. The non-topcut conditions of the practical tooth profile on epicycloid groove and hypocycloid groove are obtained by analysis under the conditions that the basic design parameters are given,cutting tool maximum feeding（ i. e. maximum groove depth）that all tooth surfaces do not appear topcut when machining epicycloid groove and hypocycloid groove is obtained. Then,the conclusion is verified by the computer graphic simulation. According to the above analysis results,for ensuring the steel ball and the tooth surface can be properly mesh,the inequality equation that the steel ball radius should be satisfied is derived,the relationship between steel ball radius and parameters is analyzed,the results show that steel ball radius increases with the increase of occurrence circle radius,with decrease of the short amplitude coefficient,and occurrence circle is larger,short amplitude coefficient is smaller,the steel ball size range is more widely. The results of research offer a theoretical gist for designing and manufacturing of real-time zero-clearance steel ball precision transmission.